Terapia fonoaudiológica na taquifemia: relato de caso - Oliveira, Cristiane Moço Canhetti de [UNESP]; Reis, Hellen Fátima dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
The speech therapy in cluttering is a subject little explored in the literature. Objective: To assess the effectiveness of a therapeutic program to reduce and control the speech rate in cluttering, by comparing the speech fluency pre- and post-therapeutic program, as the speech rate and disfluencies frequency. Methods: The participants were one cluttering, male, aged 16 years. The diagnosis of cluttering was conducted by an experienced therapist in the area. The participant showed an increase in the number of other disfluencies and increased speech rate. The following procedures were used: specific medical history, assessment of fluency and application of Predictive Instrument cluttering pre and post-therapy and application of therapeutic program (8 sessions). Results: Comparing the data extracted from the patient's speech samples before and after the proposed observed that aspects of speech such as continuity, speed, pace and motortemporal coordination showed positive responses to the applied model of intervention, the patient demonstrated greater ease and control both the articulation and breathing as the speech rate.

A intervenção fonoaudiológica na taquifemia é uma temática pouco explorada na literatura. Objetivo: verificar a efetividade de um programa terapêutico para reduzir e controlar a taxa de elocução na taquifemia, por meio da comparação da fluência da fala pré- e pós-programa terapêutico, quanto à taxa de elocução e frequência de disfluências. Métodos: Participaram da pesquisa um taquifêmico, do gênero masculino, na faixa etária de 16 anos. O diagnóstico de taquifemia foi realizado por uma fonoaudióloga experiente na área. O participante apresentou aumento na quantidade de outras disfluências e velocidade de fala aumentada. Foram utilizados os seguintes procedimentos: história clínica específica, avaliação da fluência e aplicação do Instrumento Preditivo da Taquifemia pré e pós-terapia e aplicação do programa terapêutico (8 sessões). Resultados: Comparando os dados extraídos das amostras de fala do paciente antes e depois do proposto, observamos que aspectos da fala como a continuidade, velocidade, ritmo e coordenação motora-temporal demonstraram respostas positivas ao modelo de intervenção aplicado, o paciente demonstrou maior desenvoltura e controle tanto da articulação e respiração quanto da velocidade de fala.
Keywords: Speech; Speech disorders; Fala; Distúrbio da fala